Therapeutic Applications of Mesenchymal Stem Cells:: A Comprehensive Review - Samadi, Pouria; Saki, Sahar; Manoochehri, Hamed; Sheykhhasan, Mohsen (Current Stem Cell Research & Therapy, 2021)
Mesenchymal Stem Cells (MSCs) are one of the most promising tools for cell therapy, that are isolated from bone marrow and many other adult tissues such as liver, cord blood, placenta, dental pulp and adipose tissue. Due to the lack of MHC class II expression on the surface of MSCs, they can also be used as a potent cell source for tissue regeneration in non-autologous cell therapy applications. Many advantages of MSCs such as their self-renewal, in vitro proliferation, rapid cell doubling capacity, anti-fibrotic, anti-apoptotic, anti-inflammatory, immunomodulatory and immunosuppressive effects, and also paracrine nature have been demonstrated in various pre– clinical studies and clinical evidence. The ability of MSCs to differentiate into multiple cell lineages, as well as the lack of ethical issues in comparison with embryonic and induced Pluripotent Stem Cells (iPSCs), has introduced them as a suitable candidate for cell therapy. This review provides a comprehensive overview of various clinical trials based on MSCs for the treatment of a variety of diseases, demonstrating their capability in the treatment of dermatological, musculoskeletal, neurological, cardiovascular, respiratory, renal, gastroenterological and urological conditions, etc.
Keywords: Mesenchymal stem cells